Cardiovascular Health and Menopause – Review Article - Shaikh Zinnat Ara Nasreen; Sabereen Huq; Saleheen Huq; Safinaz Shahreen (International Journal of Pharma and Bio Sciences, 2020)
Menopause may produce some bothersome symptoms like hot flushes, night sweats, palpitation, osteoporosis and GSM but it can also be the start of new and rewarding phase of women’s life to guard against major health risks like heart disease and osteoporosis. Heart disease risk rises for everyone as they age, beyond menopause, risk of CVD (Cardiovascular diseases) increases dramatically. In young women who have early menopause and not taking MHT (Menopause hormone therapy), their risk of CVD is very high and it becomes the leading killer of women. A decline of estrogen may be the factor in CVD but other risk factors are Smoking, Diabetes, Raised BP, high LDL, Obesity, Sedentary lifestyle and family History. The incidence of CVD is 9 times more than breast cancer. Therefore women need to adopt strategies to prevent CVD as soon as they approach menopause. MHT can be useful in controlling the vasomotor symptoms and preventing osteoporosis. But there is still debate as to its role of primary prevention of cardiovascular disease. Evidence from Systematic review of observational studies suggest that MHT may have beneficial effects in reducing the incidence of CVD events in post menopausal women. Benefits of MHT depend on timing, of initiation, dose and duration of the drug. Micro ionized progesterone maybe used. We have reviewed different studies to know how menopause is related to CVD, how to prevent that, and the role of MHT with regard to cardiovascular health using literatures search from MEDLINE, NICE guidelines, PUBMED, WebMD, American heart association health topics, IMS recommendation, Google Scholar and journals- Climacteric and others.